PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN SOFYAN FROZEN - Annisa Safitri; Fatimatu Zahroh; Rafi Naufaliadi; Ramadhon Tricahyo Nugroho; Mohammad Sofyan; Nur Fitri Rahmawati; Anita Maulina (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The purpose of this study was to analyze the effect of each variable Product Quality, Service Quality, and Customer Experience on Customer Satisfaction in Sofyan Frozen on the Shopee platform. This research uses SPSS 20 program. The analysis technique uses validity, reliability, classical assumptions with hypotheses, and multiple linear analysis. The results showed that the variables of Product Quality, Service Quality, and Customer Experience had a significant effect on Sofyan Frozen's customer satisfaction. Product Quality, Service Quality, and Customer Experience simultaneously have a significant effect on Sofyan Frozen's customer satisfaction. The three independent variables greatly affect Sofyan Frozen's customer satisfaction. The Adjusted R square figure of 0.913 indicates that 91.3% of customer satisfaction can be explained by the three independent variables used in the regression equation. While the remaining 8.7% is explained by other variables not included in this research model